Enhancing yield and nutritional quality of sweet potato through genotype selection and selenium application - Liao, Qing; Xing, Ying; Pan, Li-Ping; Chen, Jin-Ping; Liu, Yong-Xian; Huang, Dong-Liang (Frontiers in Plant Science, 2025)
Selenium (Se) is an essential micronutrient for human health, but its widespread deficiency remains a major public health concern worldwide. Biofortification of staple crops, such as sweet potato (Ipomoea batatas), offers a sustainable strategy to improve dietary Se intake. This study systematically evaluated the capacity for natural Se accumulation in 12 major local sweet potato varieties in Guangxi, China. In addition, the effects of different Se application methods and dosages, soil application (10 L/hm2 and 20 L/hm2), foliar spraying (1.5 L/hm2 and 3.0 L/hm2), and combined soil and foliar application, were investigated on yield and quality parameters in two representative varieties: Guiziweishu 1 (high Se accumulator) and Fushu 404 (low Se accumulator). Significant genotypic variation in Se accumulation was observed, with Guiziweishu 1 exhibiting the highest tuber Se content (0.0139 mg/kg), while Fushu 404 had the lowest (0.0030 mg/kg). However, none of the varieties met the local standard for Se-rich agricultural products (0.02–0.20 mg/kg), highlighting the need for exogenous Se supplementation. Field trials demonstrated that all Se application treatments significantly increased tuber Se content, with foliar and combined soil+foliar applications showing the greatest effectiveness. In Guiziweishu 1, all Se treatments except T1 achieved the Se-rich standard, whereas in Fushu 404, only T4 and T6 reached this threshold. Yield improvements were also observed, with the combined soil+foliar treatment (T6) resulting in the highest increases in both fresh yield (24.22% for Guiziweishu 1, 13.06% for Fushu 404) and dry tuber yield (36.52% and 25.77%, respectively), relative to the control group. Se application further enhanced starch and anthocyanin content in Guiziweishu 1, whereas the effects were less pronounced in Fushu 404. These findings underscore the importance of varietal selection and optimized agronomic practices for effective Se biofortification in sweet potato, providing a theoretical and practical basis for developing Se-riched sweet potato cultivation and contributing to improved crop quality, yield, and public health in Se-deficient regions.